READING IN ENGLISH BY CHILDREN IN KOREA: FREQUENCY, EFFECTIVENESS, AND BARRIERS - Kyung Sook Cho Sook Cho; Eun Jin Park; Stephen Krashen (Indonesian JELT, 2008)
A study of the English non-textbook reading of fourth graders in Korea revealed that about 80% had done at least some reading, confirming that there is enthusiasm for English reading. About half, however, had read only five books or fewer. Non-readers said that the reason they did not read in English was the difficulty of English texts. Those who read more did better on a test of English spelling and vocabulary. Keywords: English non-textbook reading; Enthusiasm for English reading; English texts; English spelling and vocabulary